Salivary miRNAs and cytokines associated with diagnosis and prognosis of oral squamous cell carcinoma - Qin, Yuxiao; Dong, Xiaodan; Li, Bo (Frontiers in Cell and Developmental Biology, 2025)
Oral squamous cell carcinoma (OSCC) is the most common malignant tumour in the oral and maxillofacial region. Early diagnosis can significantly improve the 5-year survival rate of patients with OSCC. Therefore, it is extremely important to differentiate OSCC patients early, easily and quickly. Human saliva contains a variety of components that can be used as biomarkers for the diagnosis and prognosis of OSCC. Studies have shown that salivary microRNAs (miRNAs) and cytokines are closely associated with the progression of OSCC. The aim of this review is to summarize the research progress of salivary biomarkers (miRNAs and cytokines) in the past 3 years, and to explore the possibility of using miRNAs and cytokines to improve the diagnosis and prognosis of OSCC.